(3edJbWGJ cJGH Gdhbha hGdUObGJs - (3eQJVi Hf eMeO Cejf GdORahdj GdCfUGQj, J (B1281 (3g` s
(3ChdgG (B:s
(3cJGH Gdhba hGdUObGJ GdJbGW Gdhba dZI GdMHS hGdJMHjS s
(3BNQgG (B:s
(3eG PcQg GdSjO ai GdJaUjd djS Ydjg TGgO ai cdeGJ GdYdeGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B201s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ MSjf Ydi eMahX (B(6) s
Keywords: (3abg GdePGgH GdCNQis